INTERNALISASI NILAI KEBAIKAN MELALUI FUNGSI KEAGAMAAN DAN PENGONDISIAN LINGKUNGAN DAN DAMPAKNYA TERHADAP KARAKTER ANAK - Dermawan, Sri; Sunarti, Euis; Herawati, Tin (Jurnal Ilmu Keluarga dan Konsumen, 2017)
Phenomenon of working mothers indicated differences the implementation of family functions that could be have different influence on the child's character. This study aimed to analyze the differences and influence of internalization of virtue values through religious function and environmental conditioning on the child's character of working mothers and nonworking mothers. This research used cross-sectional design and conducted in Babakan Village, Dramaga Sub District, Bogor District. The participants of this study were 121 mothers and their children (9-11 years old) selected by stratified random sampling technique. The results showed that working mothers had higher internalization of virtue values through religious functions (faith dimension) and also their child had higher character than nonworking mothers. Working mothers have a higher education so they have more ability to internalize the virtue values to their children. The result also found that family characteristic, internalization of virtue values through religious function, and environmental conditioning had a direct positive effect on child's character. This research recommends that government, universities, NGOs, and society to give support the family resilience so the family is able to perform their duties and functions optimally, especially in internalizing of virtue value to enhancement child's character through religious function and environmental conditioning.